A differential diagnosis of inherited endocrine tumors and their tumor counterparts - Sergio P. A. Toledo; Delmar M. Lourenço Jr; Rodrigo A. Toledo (Clinics, 2013)
Inherited endocrine tumors have been increasingly recognized in clinical practice, although some difficulties still exist in differentiating these conditions from their sporadic endocrine tumor counterparts. Here, we list the 12 main topics that could add helpful information and clues for performing an early differential diagnosis to distinguish between these conditions. The early diagnosis of patients with inherited endocrine tumors may be performed either clinically or by mutation analysis in at-risk individuals. Early detection usually has a large impact in tumor management, allowing preventive clinical or surgical therapy in most cases. Advice for the clinical and surgical management of inherited endocrine tumors is also discussed. In addition, recent clinical and genetic advances for 17 different forms of inherited endocrine tumors are briefly reviewed.